psychological attitudes of physical education teachers (graduates of institutes of physical education) in primary schools towards the teaching profession. A field study in the state of Khenchela. - Chermime , mourad; kroum, Bachir (sports creativity, 2024)
The study aimed to investigate the psychological attitudes of physical education teachers in Khenchela towards their profession. The researcher distributed an attitude scale among a sample of 18 teachers working in some primary schools in Khenchela. The researcher employed a descriptive approach and relied on statistical methods such as mean, standard deviation, Pearson correlation coefficient, and Cronbach's alpha. The study concluded that physical education teachers hold positive attitudes.